2022
DOI: 10.1039/d1mh01813b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antibacterial function of a supramolecular artificial receptor-modified macrophage (SAR-Macrophage)

Abstract: SAR-Macrophage was developed to rapidly recognize E. coli through strong host–guest interactions, thus improving the internalization of E. coli, which subsequently induced M1 polarization of macrophages to kill bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Inspired by the attractive chimeric antigen receptor macrophage (CAR-macrophage), Wang and co-workers put forward a reminiscent concept named supramolecular artificial receptor-modified macrophage (SAR-macrophage) by modifying macrophage with CB [7] on the surface by ligand (DSPE-PEG-CB [7]) insertion (Figure 9D). [72] SARmacropahge exhibited enhanced recognition and engulfment of bacteria tagged with a guest molecule (ADA). Both in vitro and in vivo results showed that SAR macrophage could dramatically enhance the identification and clearance of E. coli, through host-guest recognition and the subsequent polarization and reactive oxygen species (ROS) generation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the attractive chimeric antigen receptor macrophage (CAR-macrophage), Wang and co-workers put forward a reminiscent concept named supramolecular artificial receptor-modified macrophage (SAR-macrophage) by modifying macrophage with CB [7] on the surface by ligand (DSPE-PEG-CB [7]) insertion (Figure 9D). [72] SARmacropahge exhibited enhanced recognition and engulfment of bacteria tagged with a guest molecule (ADA). Both in vitro and in vivo results showed that SAR macrophage could dramatically enhance the identification and clearance of E. coli, through host-guest recognition and the subsequent polarization and reactive oxygen species (ROS) generation.…”
Section: Methodsmentioning
confidence: 99%
“…Inspired by the attractive chimeric antigen receptor macrophage (CAR‐macrophage), Wang and co‐workers put forward a reminiscent concept named supramolecular artificial receptor‐modified macrophage (SAR‐macrophage) by modifying macrophage with CB[7] on the surface by ligand (DSPE‐PEG‐CB[7]) insertion (Figure 9D) [72] . SAR‐macropahge exhibited enhanced recognition and engulfment of bacteria tagged with a guest molecule (ADA).…”
Section: Covalent Cb[n]‐based Polymersmentioning
confidence: 99%
“…The promoted recognition and capture of E. coli induced the M1 polarization of macrophages to generate ROS and effectively killed the intracellular bacteria. This work provides a supramolecular cell-engineering approach for potential antibacterial applications [ 108 ].…”
Section: Supramolecular Self-assembly For the Improvement Phagocytosi...mentioning
confidence: 99%
“…Cyclodextrins (CDs), a class of cyclic oligomers of glucose, with excellent biocompatibility, extreme non-immunogenicity, and low toxicity in vivo, are widely used in many pharmaceutical products. [24][25][26][27] Its special cavity structure can effectively protect the functional groups of payloads and enhance their water solubility. Using 2-methoxypropene (MP) as an engineering reagent, acetalated cyclodextrin materials (Ac-CD) with acid responsiveness can be facilely prepared.…”
Section: Introductionmentioning
confidence: 99%